A review of national guidelines for management of COPD in Europe. Issue 2 (21st January 2016) - Miravitlles, Marc; Vogelmeier, Claus; Roche, Nicolas; Halpin, David; Cardoso, João; Chuchalin, Alexander G.; Kankaanranta, Hannu; Sandström, Thomas; Śliwiński, Paweł; Zatloukal, Jaromir; Blasi, Francesco
The quality of care can be improved by the development and implementation of evidence-based treatment guidelines. Different national guidelines for chronic obstructive pulmonary disease (COPD) exist in Europe and relevant differences may exist among them. This was an evaluation of COPD treatment guidelines published in Europe and Russia in the past 7 years. Each guideline was reviewed in detail and information about the most important aspects of patient diagnosis, risk stratification and pharmacotherapy was extracted following a standardised process. Guidelines were available from the Czech Republic, England and Wales, Finland, France, Germany, Italy, Poland, Portugal, Russia, Spain and Sweden. The treatment goals, criteria for COPD diagnosis, consideration of comorbidities in treatment selection and support for use of long-acting bronchodilators, were similar across treatment guidelines. There were differences in measures used for stratification of disease severity, consideration of patient phenotypes, criteria for the use of inhaled corticosteroids and recommendations for other medications ( e.g. theophylline and mucolytics) in addition to bronchodilators. There is generally good agreement on treatment goals, criteria for diagnosis of COPD and use of long-acting bronchodilators as the cornerstone of treatment among guidelines for COPD management in Europe and Russia. However, there are differences in the definitions of patient subgroups and other recommended treatments. There are important differences between European national COPD guidelines http://ow.ly/U2P4y